Regulatory roles of copper metabolism and cuproptosis in human cancers - Wang, Zhe; Jin, Dekui; Zhou, Shuaishuai; Dong, Niujing; Ji, Yuting; An, Peng; Wang, Jiaping; Luo, Yongting; Luo, Junjie (Frontiers in Oncology, 2023)
Copper is an essential micronutrient for human body and plays a vital role in various biological processes including cellular respiration and free radical detoxification. Generally, copper metabolism in the body is in a stable state, and there are specific mechanisms to regulate copper metabolism and maintain copper homeostasis. Dysregulation of copper metabolism may have a great connection with various types of diseases, such as Wilson disease causing copper overload and Menkes disease causing copper deficiency. Cancer causes the highest mortality rate in the world due to the unlimited proliferation potential, apoptosis escape and immune escape properties. Copper is thought to have a great connection with cancer, such as elevated levels in cancer tissue and serum. Copper also affects tumor progression by affecting angiogenesis, metastasis and other processes. Notably, cuproptosis is a novel form of cell death that may provide novel targeting strategies for developing cancer therapy. Copper chelators and copper ionophores are two copper coordinating compounds for the treatment of cancer. This review will explore the relationship between copper metabolism and cancers, and clarify copper metabolism and cuproptosis for cancer targeted therapy.